2007
DOI: 10.1348/096317906x164927
|View full text |Cite
|
Sign up to set email alerts
|

Customer-induced stress in call centre work: A comparison of audio- and videoconference

Abstract: Call centre work was simulated in an experiment with 96 experienced call centre agents. The experimental design comprised two factors. First, agents communicated with customers either via phone, pc‐videoconference or pc‐videoconference with additional instructions increasing time pressure. The second experimental factor varied customer behaviour: half of the customers were friendly whereas the other half were rude. Several indicators of strain (e.g. emotional dissonance, tiredness) were assessed by self‐report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 37 publications
(46 reference statements)
1
72
0
2
Order By: Relevance
“…Anxiety has also been linked with customer mistreatment because customer mistreatment creates ambiguity about how employee performance and well-being will be affected (Wegge, Van Dick, & Von Bernstorff, 2010;Zhan, Wang, & Shi, 2013). Furthermore, an array of other negative emotions, including sadness, fear, frustration, disappointment, hurt, guilt, and shame Rupp et al, 2007;Volmer, Binnewies, Sonnentag, & Niessen, 2012;Wegge, Vogt, & Wecking, 2007;Yang & Diefendorff, 2009) have also been examined as affective consequences of customer mistreatment.…”
Section: Customer Mistreatment As An Affective Work Eventmentioning
confidence: 99%
See 2 more Smart Citations
“…Anxiety has also been linked with customer mistreatment because customer mistreatment creates ambiguity about how employee performance and well-being will be affected (Wegge, Van Dick, & Von Bernstorff, 2010;Zhan, Wang, & Shi, 2013). Furthermore, an array of other negative emotions, including sadness, fear, frustration, disappointment, hurt, guilt, and shame Rupp et al, 2007;Volmer, Binnewies, Sonnentag, & Niessen, 2012;Wegge, Vogt, & Wecking, 2007;Yang & Diefendorff, 2009) have also been examined as affective consequences of customer mistreatment.…”
Section: Customer Mistreatment As An Affective Work Eventmentioning
confidence: 99%
“…Thus, service employees experiencing greater job demands are less likely to deliver high-quality service (van Jaarsveld et al, 2010). For instance, Wegge et al (2007) observed that service employees under greater time pressure experienced more strain and spent less time talking to customers.…”
Section: Service Encounter-level Customer Mistreatment à Antecedentsmentioning
confidence: 99%
See 1 more Smart Citation
“…These employees generally must suppress inner feelings of anger, respond with a smile and fulfill customer needs even without the desire to do so. Organizations usually monitor employees to ensure they do not respond in retaliatory or unhappy ways (Wegge et al, 2007) and insist that they fake emotions during difficult customer encounters. If employees feel irritated, mad or a desire to walk away, but must respond with a "smile" or pleasant tone, such job-related behaviors cause emotional dissonance (Wegge et al, 2007).…”
Section: Emotional Dissonancementioning
confidence: 99%
“…Several researchers underlined that customer management has not been investigated enough as a source of stress in the literature of work-related stress, although 22% of negative events reported by workers occurred when dealing with ‘problem customers’ and some anger-provoking events related to mistreatment by customers [16,17]. …”
Section: Introductionmentioning
confidence: 99%